ANALISIS KINERJA KEUANGAN DENGAN PENDEKATAN EVA (STUDI KASUS : PT. SMARTFREN TELECOM, TBK PERIODE 2013-2015) - Sari, Ratna Kurnia (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2018)
The most important factor to be able to see the development of a Telecommunications company lies in its financial elements, because of these elements can be evaluated whether the policies adopted a company is correct or not, given the complexity of problems that can lead to bankruptcy due to the number of companies that ultimately out of business due to financial factors not healthy. While the goal to be achieved in this research is to know the financial performance of PT. Smartfren Telecom, Tbk reviewed based on the EVA approach. The data analysis method used here refers to a comparative descriptive analysis, in which the financial statements will be analyzed in terms of NOPAT, WACC, Invested Capital, Capital Charges and EVA in order to obtain a comparison of the results in each year, so that it will show the financial and performance levels of the company. While the data source used in this study is secondary data in the form of corporate financial statement documents from 2013 to 2015 obtained from the website of PT. Smartfren Telecom, Tbk is www.smartfren.com. The results obtained are that the largest EVA value at PT. Smartfren Telecom, Tbk occurs in 2015. This is due to the NOPAT value that is greater than the previous year and its Capital Charge value is also greater than the other period. From here it can also be seen that the value of EVA less than 0 where it shows no economic value-added for the company, so get negative results. And if this happens continuously, it will affect the creditors and shareholders to invest. Keywords: financial performance, economic value added, telecommunication company